FLYPAPER EFFECT PADA DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH KABUPATEN/KOTA DI PROVINSI BALI - Meilyana Putri Setiawan; Komang Krishna Yogantara (Journal Research of Accounting, 2022)
The aims of this study was to determine how the influence of the General Allocation Fund and Regional Original Revenue on Regional Expenditures and whether there was a Flypaper Effect. This research was conducted at the Regency/City Government in Bali Province with a budget period of 2016 to 2020. The method used in this research is the documentation method. The population in this study were all regencies/cities in the province of Bali. In this study using a saturated sampling technique, which uses the entire population as a sample in the study. The analytical tool in this study uses multiple linear regression analysis to find out whether the General Allocation Fund and Regional Original Revenue have an effect on Regional Expenditures. The results of this study indicate that (1) General Allocation Funds have no effect on Regional Expenditures, (2) Regional Original Revenues have an effect on Regional Expenditures, (3) There is no Flypaper effect on General Allocation Funds and Regional Original Revenues on Regency/City Regional Expenditures in Bali province.